(untitled) (International journal of artificial intelligence, 2025)
This article examines the environmental challenges of ensuring the safe storage, transportation, and disposal of radioactive waste today. The problem of nuclear waste disposal and reforming comprehensive radioactive waste disposal measures is one of the most dangerous in the modern world. The disposal and disposal of radioactive waste from nuclear power plants is becoming particularly pressing today, requiring the selection of optimal disposal sites and methods. Methods for the disposal of low-, intermediate-, and high-level waste accumulated at nuclear power plants are also discussed.